Study of the Purchasing Intention of Tourists for Guizhou Intangible Cultural Heritage Batik Products - Ya Huang; Jacky Mong Kwan Watt (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The abstract on the purchasing intention of tourists for Guizhou's intangible cultural heritage batik products explores the interplay of cultural significance, consumer attitudes, and social influence. It highlights how the rich history and craftsmanship associated with batik create a strong emotional connection for tourists, enhancing their willingness to purchase these items as authentic souvenirs. Positive consumer attitudes, shaped by prior experiences and appreciation for cultural heritage, further contribute to purchase intentions. Additionally, social influence plays a crucial role, as recommendations from peers and social media endorsements significantly impact tourists' perceptions and decisions. The study underscores the importance of effectively promoting these cultural products through storytelling, community engagement, and leveraging social proof to boost sales and preserve cultural traditions through the survey of 390 Guizhou residents.